KONSTRUKSI BERITA PERNIKAHAN SIRI DI MEDIA ONLINE:: Analisis Framing Kompas.com dan Republika.co.id pada Tahun 2022 - yani, sri mul (Program Study of Islamic Communication and Broadcasting, Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
The phenomenon of unregistered marriage raises pros and cons in a multicultural society. This research uses a qualitative descriptive approach with framing analysis by Zhongdang Pan and Gerald M. Kosicki. Identifying through the four structures of syntax, script, thematic, and rhetorical. The final step is examined from the perspective of Islamic journalism. This research aims to determine the construction of news in the online media Kompas.com and Republika.co.id. Next, it is analyzed using an Islamic journalism perspective. The object of the research is 6 news stories about serial marriages in the period March-November 2022. This is to see the differences in media construction in framing news. The results of this research are as follows: first, in the construction aspect Kompas.com and Republika.co.id as a whole both convey information about unregistered marriages which should be avoided by the public. Second, differences in media construction are influenced by respective ideologies. Kompas.com, which has nationalist characteristics, has widely reported on the negative impacts of unregistered marriages. Republika.co.id, which has an Islamic ideology, raised the news with a religious approach. On aspects of Islamic journalism, Kompas.com has not fully implemented the values ​​of the concept of Islamic journalism. Meanwhile, Republika.co.id as a whole has prioritized Islamic concepts over news construction.